An RNA molecular switch: Intrinsic flexibility of 23S rRNA Helices 40 and 68 5'-UAA/5'-GAN internal loops studied by molecular dynamics methods - Réblová, Kamila; Střelcová, Zora; Kulhánek, Petr; Beššeová, Ivana; Mathews, David H; Nostrand, Keith Van; Yildirim, Ilyas; Turner, Douglas H; Sponer, Jiří (Journal of chemical theory and computation, 2010)
Functional RNA molecules such as ribosomal RNAs frequently contain highly conserved internal loops with a 5'-UAA/5'-GAN (UAA/GAN) consensus sequence. The UAA/GAN internal loops adopt distinctive structure inconsistent with secondary structure predictions. The structure has a narrow major groove and forms a trans Hoogsteen/Sugar edge (tHS) A/G base pair followed by an unpaired stacked adenine, a trans Watson-Crick/Hoogsteen (tWH) U/A base pair and finally by a bulged nucleotide (N). The structure is further stabilized by a three-adenine stack and base-phosphate interaction. In the ribosome, the UAA/GAN internal loops are involved in extensive tertiary contacts, mainly as donors of A-minor interactions. Further, this sequence can adopt an alternative 2D/3D pattern stabilized by a four-adenine stack involved in a smaller number of tertiary interactions. The solution structure of an isolated UAA/GAA internal loop shows substantially rearranged base pairing with three consecutive non-Watson-Crick base pairs. Its A/U base pair adopts an incomplete cis Watson-Crick/Sugar edge (cWS) A/U conformation instead of the expected Watson-Crick arrangement. We performed 3.1 µs of explicit solvent molecular dynamics (MD) simulations of the X-ray and NMR UAA/GAN structures, supplemented by MM-PBSA free energy calculations, locally enhanced sampling (LES) runs, targeted MD (TMD) and nudged elastic band (NEB) analysis. We compared parm99 and parmbsc0 force fields and net-neutralizing Na(+) vs. excess salt KCl ion environments. Both force fields provide a similar description of the simulated structures, with the parmbsc0 leading to modest narrowing of the major groove. The excess salt simulations also cause a similar effect. While the NMR structure is entirely stable in simulations, the simulated X-ray structure shows considerable widening of the major groove, loss of base-phosphate interaction and other instabilities. The alternative X-ray geometry even undergoes conformational transition towards the solution 2D structure. Free energy calculations confirm that the X-ray arrangement is less stable than the solution structure. LES, TMD and NEB provide a rather consistent pathway for interconversion between the X-ray and NMR structures. In simulations, the incomplete cWS A/U base pair of the NMR structure is water mediated and alternates with the canonical A-U base pair, which is not indicated by the NMR data. Completion of full cWS A/U base pair is prevented by the overall internal loop arrangement. In summary, the simulations confirm that the UAA/GAN internal loop is a molecular switch RNA module that adopts its functional geometry upon specific tertiary contexts.